Two Metals Are Better Than One in the Gold Catalyzed Oxidative Heteroarylation of Alkenes - Tkatchouk, Ekaterina (2011)
We present a detailed study of the mechanism for oxidative heteroarylation, based on DFT calculations and experimental observations. We propose binuclear Au(II)-Au(II) complexes to be key intermediates in the mechanism for gold catalyzed oxidative heteroarylation. The reaction is thought to proceed via a gold redox cycle involving initial oxidation of Au(I) to binuclear Au(II)-Au(II) complexes by Selectfluor, followed by heteroauration and reductive elimination. While it is tempting to invoke a transmetalation/reductive elimination mechanism similar to that proposed for other transition metal complexes, experimental and DFT studies suggest that the key C-C bond forming reaction occurs via a bimolecular reductive elimination process (devoid of transmetalation). In addition, the stereochemistry of the elimination step was determined experimentally to proceed with complete retention. Ligand and halide effects played an important role in the development and optimization of the catalyst; our data provides an explanation for the ligand effects observed experimentally, useful for future catalyst development. Cyclic voltammetry data is presented that supports redox synergy of the Au···Au aurophilic interaction. The monometallic reductive elimination from mononuclear Au(III) complexes is also studied from which we can predict a ~15 kcal/mol advantage for bimetallic reductive elimination.